Phytochemical and Biological Effects of Sesamum indicum L.- A Review - Rashed, Khaled (Plantae Scientia, 2022)
Sesamum indicum L. is from Family Pedaliaceae. It plays an important role in ancient culture and modern system of medicine. It is commonly known as sesame. It is cultivated throughout India, mainly for its seeds and oil. The plant traditionally used in the treatment of hemorrhoids, dysentery, constipation, cough, amenorrhea, dysmenorrhea and ulcers. It also has antifungal, anticancer, antitumor, antiatherosclerotic activity. The total alcoholic extracts of all residual aerial parts of this plant show antioxidant, anticancer, antiaging and anticoagulant activities.